2020
DOI: 10.1158/2159-8290.cd-19-0622
|View full text |Cite
|
Sign up to set email alerts
|

Plasma DNA End-Motif Profiling as a Fragmentomic Marker in Cancer, Pregnancy, and Transplantation

Abstract: There is much recent research interest in the molecular characteristics of cell-free DNA (cf DNA) in plasma. One such characteristic is the fragmentation patterns of cfDNA, including information regarding fragment sizes (1), nucleosome relationships (2, 3), and end points (4, 5). This area of research can be broadly named "fragmentomics" (6). cfDNA molecules are known to circulate as short fragments (1, 7) originating from different cell types, including various normal organ systems aBstRact Plasma DNA fragmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
229
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 198 publications
(267 citation statements)
references
References 26 publications
5
229
3
Order By: Relevance
“…Furthermore, the shorter jagged ends were accompanied with a higher GC content (Supplemental Fig. S4), which was consistent with the fact that plasma DNA ends were enriched with the "CC" motif (Chandrananda et al 2015;Serpas et al 2019;Jiang et al 2020). Figure 5B shows that the mean lengths of jagged ends varied according to different sizes of plasma DNA fragments.…”
Section: Evaluation Of the Incorporation Of Methylated Cytosines In Tsupporting
confidence: 79%
See 3 more Smart Citations
“…Furthermore, the shorter jagged ends were accompanied with a higher GC content (Supplemental Fig. S4), which was consistent with the fact that plasma DNA ends were enriched with the "CC" motif (Chandrananda et al 2015;Serpas et al 2019;Jiang et al 2020). Figure 5B shows that the mean lengths of jagged ends varied according to different sizes of plasma DNA fragments.…”
Section: Evaluation Of the Incorporation Of Methylated Cytosines In Tsupporting
confidence: 79%
“…Such preferred ends were also shown to be related to the tissue of origin of plasma DNA (Chan et al 2016;Jiang et al 2018). Furthermore, certain motifs were preferentially present at the ends of plasma DNA molecules (Serpas et al 2019;Jiang et al 2020). Such end motif analysis revealed that DNASE1L3 (deoxyribonuclease 1-like 3), an endonuclease, plays an important role in the fragmentation of plasma DNA (e.g., the forming of the "CCCA" end motif of plasma DNA molecules), as elucidated by a Dnase1l3 deletion mouse model (Serpas et al 2019).…”
mentioning
confidence: 86%
See 2 more Smart Citations
“…Unfortunately, serial assessment of MYCN amplification of tumor is not possible due to the lack of primary tumor tissue and heterogeneity of tumor in NB. Nowadays, liquid biopsy test is emerging as a promising and repeatable method to examine tumor load in clinic [24,26,[44][45][46]. Using blood cfDNA from patients with NB sheds light on predicting MYCN amplification repeatedly [34][35][36].…”
Section: Discussionmentioning
confidence: 99%